Polythiophene and oligothiophene systems modified by TTF electroactive units for organic electronics - Kanibolotsky, Alexander L.; Findlay, Neil J.; Skabara, Peter J. (Beilstein Journal of Organic Chemistry, 2015)
The aim of this review is to give an update on current progress in the synthesis, properties and applications of thiophene-based conjugated systems bearing tetrathiafulvalene (TTF) units. We focus mostly on the synthesis of poly- and oligothiophenes with TTF moieties fused to the thiophene units of the conjugated backbone either directly or via a dithiin ring. The electrochemical behaviour of these materials and structure–property relationships are discussed. The study is directed towards the development of a new type of organic semiconductors based on these hybrid materials for application in organic field effect transistors and solar cells.
Keywords: donor; oligothiophene; organic electronics; polythiophene; semiconductor; tetrathiafulvalene

(untitled) - Skabara, P. J.; Arlin, J.-B.; Geerts, Y. H. (Adv. Mater., 2013)

(untitled) - Chen, T. A.; Rieke, R. D. (J. Am. Chem. Soc., 1992)

(untitled) - McCullough, R. D.; Tristram-Nagle, S.; Williams, S. P.; Lowe, R. D.; Jayaraman, M. (J. Am. Chem. Soc., 1993)

(untitled) - Groenendaal, L.; Jonas, F.; Freitag, D.; Pielartzik, H.; Reynolds, J. R. (Adv. Mater., 2000)

(untitled) - Dang, M. T.; Hirsch, L.; Wantz, G.; Wuest, J. D. (Chem. Rev., 2013)

(untitled) - Sirringhaus, H.; Tessler, N.; Friend, R. H. (Science, 1998)

(untitled) - Cho, S.; Lee, K.; Yuen, J.; Wang, G.; Moses, D.; Heeger, A. J.; Surin, M.; Lazzaroni, R. (J. Appl. Phys., 2006)

(untitled) - Zotti, G.; Zecchin, S.; Schiavon, G.; Berlin, A.; Pagani, G.; Canavesi, A. (Chem. Mater., 1995)

(untitled) - Schäferling, M.; Bäuerle, P. (J. Mater. Chem., 2004)

(untitled) - Iraqi, A.; Crayston, J. A.; Walton, J. C. (J. Mater. Chem., 1998)

(untitled) - Skabara, P. J.; Serebryakov, I. M.; Perepichka, I. F.; Sariciftci, N. S.; Neugebauer, H.; Cravino, A. (Macromolecules, 2001)

(untitled) - Skabara, P. J.; Berridge, R.; Serebryakov, I. M.; Kanibolotsky, A. L.; Kanibolotskaya, L.; Gordeyev, S.; Perepichka, I. F.; Sariciftci, N. S.; Winder, C. (J. Mater. Chem., 2007)

(untitled) - Goldenberg, L. M.; Skabara, P. J.; Roberts, D. M.; Berridge, R.; Ortí, E.; Viruela, P. M.; Pou-Amérigo, R. (J. Mater. Chem., 2000)

(untitled) - Berridge, R.; Wright, S. P.; Skabara, P. J.; Dyer, A.; Steckler, T.; Argun, A. A.; Reynolds, J. R.; Harrington, R. W.; Clegg, W. (J. Mater. Chem., 2007)

(untitled) - Palermo, E. F.; Darling, S. B.; McNeil, A. J. (J. Mater. Chem. C, 2014)

(untitled) - Chan, S.-H.; Lai, C.-S.; Chen, H.-L.; Ting, C.; Chen, C.-P. (Macromolecules, 2011)

(untitled) - Bijleveld, J. C.; Zoombelt, A. P.; Mathijssen, S. G. J.; Wienk, M. M.; Turbiez, M.; de Leeuw, D. M.; Janssen, R. A. J. (J. Am. Chem. Soc., 2009)

(untitled) - Zhang, K.; Tieke, B.; Forgie, J. C.; Skabara, P. J. (Macromol. Rapid Commun., 2009)

(untitled) - Zhang, K.; Tieke, B.; Forgie, J. C.; Vilela, F.; Parkinson, J. A.; Skabara, P. J. (Polymer, 2010)

(untitled) - Zhang, K.; Tieke, B.; Forgie, J. C.; Vilela, F.; Skabara, P. J. (Macromolecules, 2012)

(untitled) - Cortizo-Lacalle, D.; Howells, C. T.; Gambino, S.; Vilela, F.; Vobecka, Z.; Findlay, N. J.; Inigo, A. R.; Thomson, S. A. J.; Skabara, P. J.; Samuel, I. D. W. (J. Mater. Chem., 2012)

(untitled) - Forgie, J. C.; Skabara, P. J.; Stibor, I.; Vilela, F.; Vobecka, Z. (Chem. Mater., 2009)

(untitled) - Wudl, F.; Wobschall, D.; Hufnagel, E. J. (J. Am. Chem. Soc., 1972)

(untitled) - Ferraris, J.; Cowan, D. O.; Walatka, V.; Perlstein, J. H. (J. Am. Chem. Soc., 1973)

(untitled) - Jérome, D. (Chem. Rev., 2004)

(untitled) - Seo, H.; Hotta, C.; Fukuyama, H. (Chem. Rev., 2004)

(untitled) - Kini, A. M.; Geiser, U.; Wang, H. H.; Carlson, K. D.; Williams, J. M.; Kwok, W. K.; Vandervoort, K. G.; Thompson, J. E.; Stupka, D. L. (Inorg. Chem., 1990)

(untitled) - Bryce, M. R.; Devonport, W.; Goldenberg, L. M.; Wang, C. (Chem. Commun., 1998)

(untitled) - Christensen, C. A.; Becher, J.; Goldenberg, L. M.; Bryce, M. R. (Chem. Commun., 1998)

(untitled) - Beeby, A.; Bryce, M. R.; Christensen, C. A.; Cooke, G.; Duclairoir, F. M. A.; Rotello, V. M. (Chem. Commun., 2002)

(untitled) - Kanibolotsky, A.; Roquet, S.; Cariou, M.; Leriche, P.; Turrin, C.-O.; de Bettignies, R.; Caminade, A.-M.; Majoral, J.-P.; Khodorkovsky, V.; Gorgues, A. (Org. Lett., 2004)

(untitled) - Kimura, H.; Konishi, K.; Muraoka, S.-y.; Shirahata, T.; Misaki, Y. (Chem. Lett., 2014)

(untitled) - Yang, X.; Zhang, D.; Zhang, G.; Zhu, D. (Sci. China: Chem., 2011)

(untitled) - Nalluri, S. K. M.; Shivarova, N.; Kanibolotsky, A. L.; Zelzer, M.; Gupta, S.; Frederix, P. W. J. M.; Skabara, P. J.; Gleskova, H.; Ulijn, R. V. (Langmuir, 2014)

(untitled) - Inagi, S.; Naka, K.; Chujo, Y. (J. Mater. Chem., 2007)

(untitled) - Kashimura, Y.; Goto, T.; Nakashima, H.; Furukawa, K.; Wang, E.; Li, H.; Hu, W.; Torimitsu, K. (Jpn. J. Appl. Phys., 2010)

(untitled) - Jia, H.-P.; Forgie, J. C.; Liu, S.-X.; Sanguinet, L.; Levillain, E.; Le Derf, F.; Sallé, M.; Neels, A.; Skabara, P. J.; Decurtins, S. (Tetrahedron, 2012)

(untitled) - Zhang, X.; Wang, C.; Lai, G.; Zhang, L.; Shen, Y. (New J. Chem., 2010)

(untitled) - Zhang, X.-C.; Wang, C.-Y.; Lai, G.-Q.; Zhang, L.; Shen, Y.-J. (Polym. Bull., 2011)

(untitled) - Zhang, L.; Li, M.; Wang, C.; Lai, G.; Shen, Y. (Polym. Bull., 2013)

(untitled) - Hou, Y.; Wan, X.; Yang, M.; Ma, Y.; Huang, Y.; Chen, Y. (Macromol. Rapid Commun., 2008)

(untitled) - Hou, Y.; Chen, Y.; Liu, Q.; Yang, M.; Wan, X.; Yin, S.; Yu, A. (Macromolecules, 2008)

(untitled) - Yamamoto, T.; Shimizu, T. (J. Mater. Chem., 1997)

(untitled) - Zotti, G.; Zecchin, S.; Schiavon, G.; Berlin, A.; Huchet, L.; Roncali, J. (J. Electroanal. Chem., 2001)

(untitled) - Roncali, J. (J. Mater. Chem., 1999)

(untitled) - Bryce, M. R.; Chissel, A. D.; Gopal, J.; Kathirgamanathan, P.; Parker, D. (Synth. Met., 1991)

(untitled) - Zhang, L.; Li, M.; Wang, C.; Wang, Y.; Shen, Y. (J. Appl. Polym. Sci., 2013)

(untitled) - Thobie-Gautier, C.; Gorgues, A.; Jubault, M.; Roncali, J. (Macromolecules, 1993)

(untitled) - Huchet, L.; Akoudad, S.; Roncali, J. (Adv. Mater., 1998)

(untitled) - Huchet, L.; Akoudad, S.; Levillain, E.; Roncali, J.; Emge, A.; Bäuerle, P. (J. Phys. Chem. B, 1998)

(untitled) - Besbes, M.; Trippé, G.; Levillain, E.; Mazari, M.; Le Derf, F.; Perepichka, I. F.; Derdour, A.; Gorgues, A.; Sallé, M.; Roncali, J. (Adv. Mater., 2001)

(untitled) - Trippé, G.; Le Derf, F.; Lyskawa, J.; Mazari, M.; Roncali, J.; Gorgues, A.; Levillain, E.; Sallé, M. (Chem. – Eur. J., 2004)

(untitled) - Sinha, J.; Lee, S. J.; Kong, H.; Swift, T. W.; Katz, H. E. (Macromolecules, 2013)

(untitled) - Skabara, P. J.; Müllen, K. (Synth. Met., 1997)

(untitled) - Skabara, P. J.; Berridge, R.; McInnes, E. J. L.; West, D. P.; Coles, S. J.; Hursthouse, M. B.; Müllen, K. (J. Mater. Chem., 2004)

(untitled) - Shu, P.; Chiang, L.; Emge, T.; Holt, D.; Kistenmacher, T.; Lee, M.; Stokes, J.; Poehler, T.; Bloch, A.; Cowan, D. (J. Chem. Soc., Chem. Commun., 1981)

(untitled) - Rovira, C.; Santalō, N.; Veciana, J. (Tetrahedron Lett., 1989)

(untitled) - Rovira, C.; Veciana, J.; Santalo, N.; Tarres, J.; Cirujeda, J.; Molins, E.; Llorca, J.; Espinosa, E. (J. Org. Chem., 1994)

(untitled) - Skabara, P. J.; Müllen, K.; Bryce, M. R.; Howard, J. A. K.; Batsanov, A. S. (J. Mater. Chem., 1998)

(untitled) - Skabara, P. J.; Serebryakov, I. M.; Roberts, D. M.; Perepichka, I. F.; Coles, S. J.; Hursthouse, M. B. (J. Org. Chem., 1999)

(untitled) - O'Connor, B. R.; Jones, F. N. (J. Org. Chem., 1970)

(untitled) - Lee, A. W. M.; Chan, W. H.; Wong, H. C. (Synth. Commun., 1988)

(untitled) - Liu, B.; Wu, B.; Xu, J.; Wu, Z.; Zhao, Y.; Zheng, X.; Wang, H. (J. Raman Spectrosc., 2010)

(untitled) - Fox, M. A.; Pan, H.-l. (J. Org. Chem., 1994)

(untitled) - Jeppesen, J. O.; Takimiya, K.; Jensen, F.; Brimert, T.; Nielsen, K.; Thorup, N.; Becher, J. (J. Org. Chem., 2000)

(untitled) - Salle, M.; Gorgues, A.; Jubault, M.; Boubekeur, K.; Batail, P. (Tetrahedron, 1992)

(untitled) - Guziec, F. S., Jr; Russo, J. M.; Torres, F. F.; Long, G. C.; Tellez, M. R. (J. Chem. Soc., Perkin Trans. 1, 1989)

(untitled) - Serebryakov, I. M.; Skabara, P. J.; Perepichka, I. F. (J. Chem. Soc., Perkin Trans. 2, 1999)

(untitled) - Vilela, F.; Skabara, P. J.; Mason, C. R.; Westgate, T. D. J.; Luquin, A.; Coles, S. J.; Hursthouse, M. B. (Beilstein J. Org. Chem., 2010)

(untitled) - Svenstrup, N.; Becher, J. (Synthesis, 1995)

(untitled) - Berridge, R.; Serebryakov, I. M.; Skabara, P. J.; Ortí, E.; Viruela, R.; Pou-Amérigo, R.; Coles, S. J.; Hursthouse, M. B. (J. Mater. Chem., 2004)

(untitled) - Kanibolotsky, A. L.; Kanibolotskaya, L.; Gordeyev, S.; Skabara, P. J.; McCulloch, I.; Berridge, R.; Lohr, J. E.; Marchioni, F.; Wudl, F. (Org. Lett., 2007)

(untitled) - Skabara, P. J.; Roberts, D. M.; Serebryakov, I. M.; Pozo-Gonzalo, C. (Chem. Commun., 2000)

(untitled) - Roncali, J. (Chem. Rev., 1997)

(untitled) - Bredas, J.-L. (Mater. Horiz., 2014)

(untitled) - Berridge, R.; Skabara, P. J.; Pozo-Gonzalo, C.; Kanibolotsky, A.; Lohr, J.; McDouall, J. J. W.; McInnes, E. J. L.; Wolowska, J.; Winder, C.; Sariciftci, N. S.; Harrington, R. W.; Clegg, W. (J. Phys. Chem. B, 2006)

Electronic, Optical and Optoelectronic Polymers and Oligomers - Skabara, P. J.; Roberts, D. M.; Ray, A. K.; Umare, S. S.; Hassan, A. K.; Nabok, A. V.; Müllen, K. (Tetrathiafulvalene Units, 2002)

(untitled) - Kotani, S.; Shiina, K.; Sonogashira, K. (J. Organomet. Chem., 1992)

(untitled) - Renaldo, A. F.; Labadie, J. W.; Stille, J. K. (Org. Synth., 1989)

(untitled) - Roncali, J. (Chem. Rev., 1992)

(untitled) - Zotti, G.; Zecchin, S.; Schiavon, G.; Louwet, F.; Groenendaal, L.; Crispin, X.; Osikowicz, W.; Salaneck, W.; Fahlman, M. (Macromolecules, 2003)

(untitled) - Kim, E.-G.; Brédas, J.-L. (J. Am. Chem. Soc., 2008)

(untitled) - Han, G. D.; Collins, W. R.; Andrew, T. L.; Bulović, V.; Swager, T. M. (Adv. Funct. Mater., 2013)

(untitled) - Holliday, S.; Ashraf, R. S.; Nielsen, C. B.; Kirkus, M.; Röhr, J. A.; Tan, C.-H.; Collado-Fregoso, E.; Knall, A.-C.; Durrant, J. R.; Nelson, J.; McCulloch, I. (J. Am. Chem. Soc., 2015)

(untitled) - Kanibolotsky, A. L.; Forgie, J. C.; Gordeyev, S.; Vilela, F.; Skabara, P. J.; Lohr, J. E.; Petersen, B. M.; Jeppesen, J. O. (Macromol. Rapid Commun., 2008)

(untitled) - Cortizo-Lacalle, D.; Arumugam, S.; Elmasly, S. E. T.; Kanibolotsky, A. L.; Findlay, N. J.; Inigo, A. R.; Skabara, P. J. (J. Mater. Chem., 2012)

(untitled) - Arumugam, S.; Cortizo-Lacalle, D.; Rossbauer, S.; Hunter, S.; Kanibolotsky, A. L.; Inigo, A. R.; Lane, P. A.; Anthopoulos, T. D.; Skabara, P. J. (ACS Appl. Mater. Interfaces, 2015)

(untitled) - Zhang, Q.; Cirpan, A.; Russell, T. P.; Emrick, T. (Macromolecules, 2009)

(untitled) - Wang, J.; Higashihara, T. (Polym. Chem., 2013)

(untitled) - Sommer, M.; Huettner, S.; Thelakkat, M. (J. Mater. Chem., 2010)

(untitled) - Mason, C. R.; Skabara, P. J.; Cupertino, D.; Schofield, J.; Meghdadi, F.; Ebner, B.; Sariciftci, N. S. (J. Mater. Chem., 2005)

(untitled) - Wright, I. A.; Skabara, P. J.; Forgie, J. C.; Kanibolotsky, A. L.; González, B.; Coles, S. J.; Gambino, S.; Samuel, I. D. W. (J. Mater. Chem., 2011)

(untitled) - Wright, I. A.; Findlay, N. J.; Arumugam, S.; Inigo, A. R.; Kanibolotsky, A. L.; Zassowski, P.; Domagala, W.; Skabara, P. J. (J. Mater. Chem. C, 2014)